2014
DOI: 10.9790/0853-13458283
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Duplication of Optic Canal: A Case Report

Abstract: Optic canal is formed by two roots of lesserwing and body of sphenoid bone. It transmits optic nerve, ophthalmic artery and periarterial sympathetic plexus. During demonstration classes for undergraduate students we observed optic canal of left orbit of the adult skull, showing a thin spicule of bone which divided optic canal into two. Unilateral presence of duplicated optic canal is very rare. This case report may be useful for surgeons and radiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Various authors conducted an extensive review of the duplicate optical canal (DOC) offers a sum number of previously reported cases. In the literature, we evidence that duplicate optic canal had been documented as an osteological study in dried human skulls and few conducted as a radiological study [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors conducted an extensive review of the duplicate optical canal (DOC) offers a sum number of previously reported cases. In the literature, we evidence that duplicate optic canal had been documented as an osteological study in dried human skulls and few conducted as a radiological study [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…(%) Zoja et al (3) (1885) 5 6 Le Double et al (4) (1903) Case report 1 2 White et al (5) (1924) 161 3 3 1.86% Whitnell et al (6) (1932) Case report 1 1 Keyes et al (7) (1935) 2187 5 5 0.22% Warwick et al (8) (1951) Case report 1 2 Kier et al (1) (1996) 450 5 5 1.2% Lang et al (9) (1977) 3 4 Choudhry et al (2) (1988) Case report 3 5 Berlis et al (10) (1992) 80 2 2 2.5% Orhan M A et al (11) (1996) 369 2 3 0.54% Singh et al (12) (2005) 435 13 20 2.98 Math AC et al (13) (2010) 316 2 4 0.63% Patil GV et al (14) (2011) 400 11 14 2.75% Mahajan A et al (15) (2012) 96 1 1 1.04% Ghai R et al (16) (2012) 194 5 7 2.57% Shinde et al (17) (2013) 100 1 1 1% Swetha et al (18) (2014) 67 3 4 4.47% Vanitha et al (19) (2014)…”
Section: Percentagementioning
confidence: 99%